Associação de sintomas depressivos sobre autoavaliação e comportamentos de saúde bucal em usuários portadores da Covid longa - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2025)
The Covid-19 pandemic has an impact of SARS-CoV-2 infection that goes far beyond the acute phase of the disease. Persistent and prolonged symptoms have been observed in several users, regardless of the severity of the disease, with an emphasis on neuropsychiatric sequelae that are now listed as the main symptoms of long Covid syndrome. These sequelae can lead to behavioral changes and concomitantly affect the oral health of these individuals. Therefore, the aim of the study was to investigate whether depressive symptoms in adult and elderly users with long Covid syndrome influence their self-assessment and oral health behaviors. This is a cross-sectional, analytical, retrospective study with a quantitative approach, developed from primary data through telephone interviews, containing sociodemographic, clinical, self-assessed health and level of functionality data of patients at a hospital in southern Brazil, from March 2020 to March 2022. Data analysis was performed using Data Mining in a Knowledge Discovery in Databases process, dimensionality reduction model and decision tree. 108 users discharged from the study hospital were included. There was a correlation between the influence of depressive symptoms on self assessment and oral health behaviors. Variables such as lack of physical exercise, functional disability, impaired mental cognition and difficulties with the domains of mobility, life activities and participation showed the ability to affect self-care and oral health behaviors in people with long Covid, especially in the group at greatest risk of severe progression due to Covid-19. The results obtained corroborate the relevance of multidisciplinary care for people with long Covid, given the variety of symptoms presented. The attention of health professionals is extremely important for the patient's recovery in general, such as physical and mental health and mainly offering a chance for a better quality of life.
Keywords: saúde bucal; depressão; unidades de terapia intensiva; síndrome de COVID 19 pós-aguda; oral health; depression; intensive care units; syndrome de post-COVID-19; Ciências da Saúde